Pedagogical small group approach in a day care center - Lonka, Saana (2016)
Lonka, Saana. 2016. Pedagogical Small Group Approach in a Day Care Center. Varhaiskasvatustieteen pro gradu -tutkielma. Jyväskylän yliopisto. Kasvatustieteiden laitos. 84 sivua + liitteet.